Characterization of ductile damage in polyethylene plate using ultrasonic testing. (September 2017) - Zhang, Yi; Ben Jar, P.-Y.; Nguyen, Kim-Cuong T.; Le, Lawrence H.
Abstract: An experimental study was conducted to explore the possibility of using ultrasound to quantify deformation-induced damage in polyethylene (PE) plate. Specimens of two gauge lengths were machined from PE plates with thickness in the range from 1.5 to 10 mm. The specimens were first stretched monotonically to various prestrain levels to vary the extent of damage introduced by the stretch. Ultrasonic testing in the through transmission mode was then conducted on the prestrained specimens to determine the time of flight, based on which ultrasonic velocity was determined. The results show that the ultrasonic velocity, normalized by the speed in the virgin plate of the same thickness, decreases with the increase of prestrain. The study also shows that, with the correction of density change by the prestrain, the normalized ultrasonic velocity can be used to determine the dependence of damage level on the prestrain which, for specimens with long gauge length, is consistent with the damage determined by mechanical testing. The study concludes that ultrasonic testing can be used as a non-destructive means to quantify deformation-induced damage evolution in PE plates.